Early reception of smallpox inoculation in Italy: insights from the correspondence of the Fellows of the Royal Society - Berti, Lucia (Diciottesimo Secolo, 2021)
In 18th-century Europe inoculation of smallpox started being practiced as a form of prevention against the disease itself. Knowledge of this practice arrived from the Ottoman Empire and reached various European countries in the 1710s. As far as Italy is concerned, the literature generally reports that the Italians took no particular interest in inoculation until the 1750s; however, very little attention has been given to the early reception of the practice in Italy. By drawing on early news items and letter exchanges between the Fellows of the Royal Society and the Italian physician and naturalist Antonio Vallisneri, the present paper wants to illustrate and comment on these early sources that showed the Italians’ opinions and attitudes towards inoculation when it was first heard about in the peninsula.